APPLICATION OF MARKOV PROCESSES AS EFFICIENT INSTRUMENT FOR MAN-AGEMENT DECISION MAKING ON THE BASIS OF ENTERPRISE BUSINESS MODEL-ING - Evgeniya R. Khabibullina (Advanced Engineering Research)
The issues concerning the potential application of Markov processes theory for efficient management decision making based on the production enterprise business modeling are considered.